(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
Natural enemies play an important role to control the pest population of a crop field by killing the pest directly or indirectly by parasitism. By knowing the dispersal ability of natural enemies could be effective biocontrol tool for controlling the harmful pest. Vegetated field margins have been suggested as a shelter of natural enemies. Natural enemies like ground beetle, rove beetle, parasitoid and spider dispersal ability from the field margin to inside the oilseed rape field was analyzed by doing this study. All insects were collected from the oilseed rape fields of Southern Sweden. This study showed that parasitoid abundance was higher near the field margin compare to the deep field. Distribution of ground beetle, rove beetle and spider was almost the same all over the field. Parasitoids could be effective to control the oilseed rape pest near the field margin as a biocontrol aspect whereas rove beetle, ground beetle and spider could be a used biocontrol tools for all over the field. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13927 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 29-36, December, 2011